The Khartoum-Omdurman conurbation: a growing megacity at the confluence of the Blue and White Nile Rivers. Issue 4 (28th July 2021) - Zerboni, Andrea; Brandolini, Filippo; Mariani, Guido S.; Perego, Alessandro; Salvatori, Sandro; Usai, Donatella; Pelfini, Manuela; Williams, Martin A.J.
ABSTRACT: Khartoum is one of the largest cities in Africa, located immediately south of the junction of the Blue and White Nile rivers in central Sudan. The growth of the Greater Khartoum-Omdurman conurbation arose – without a proper urban plan – from the agricultural wealth created through the completion of three dams, and mostly in the last three decades. Urban expansion was enabled by and helped to enhance the major agricultural expansion of the Gezira clay plains located to the south between the lower Blue and White Nile rivers. The region has been a focus of human settlement for at least 8, 000 years, initially by semi-sedentary groups with a fishing-hunting-gathering lifestyle and later by Neolithic groups as shown by hundreds of archaeological sites. Today, Khartoum is a desert city, still very vulnerable to floods triggered by intense convectional storms. Such extreme events may become more common in future, representing a major geomorphological hazard. Moreover, uncontrolled urban and agricultural development is threatening most of the cultural heritage of the region.